The Effect of CEO Power on Firm Performance Moderated by Corporate Social Responsibility (CSR) Disclosure (Empirical Evidence in Manufacturing Companies Listed on Indonesia Stock Exchange (IDX) For Period 2018-2020) - Safira Alifah; Puji Harto (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to examine the effect of CEO power on firm performance and the moderating influence of Corporate Social Responsibility (CSR) disclosure on the relationship between CEO power and firm performance. Indicator of CEOs Power studied were the CEO ownership and the CEO tenure in the company. The firm performance studied with the calculation of Return on Assets (ROA). This study is conducted by quantitative methods using secondary data. The population is the manufacturing company listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2020, and the samples were taken by the purposive sampling method with linear regression analysis technique through the SPSS program. The sample used in this study were 89 companies with 256 observations. The results of the hypothesis test indicate that the CEO Power with CEO ownership and also CEO tenure as indicators are positively affect the firm performance with return on assets (ROA) calculated. The Corporate Social Responsibility (CSR) disclosure moderates the relationship between the CEO ownership and firm performance. Meanwhile, Corporate Social Responsibility (CSR) disclosure does not moderate the relationship between the CEO tenure and firm performance.